AI Awareness Program To Equip Students With Digital Business Skills For Post-Graduation - Lisda Fitriana Masitoh; Intan Kumalasari; Okta Irawati; Raditia Vindua; Eka Sri Rahayu; Ria Ester (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) technology has fundamentally transformed the global job market landscape, where the World Economic Forum projects that nine out of ten future jobs will require basic to intermediate digital skills. However, traditional religious educational institutions such as Maahad Tahfiz Al-Quran Darul Falah in Selangor, Malaysia, still face challenges regarding limited practical digital literacy and technology integration in the entrepreneurship curriculum for graduating students. This International Community Service (PKM) program aims to equip students with a deep understanding and practical skills in leveraging the AI ecosystem to build digital businesses and establish careers as digital freelancers post-graduation. The service partner is Maahad Tahfiz Al-Quran Darul Falah Selangor, targeting 45 final-year students. The implementation method was comprehensively designed based on Asset-Based Community Development (ABCD), incorporating initial observation, interactive lectures, hands-on workshops on AI tools (Generative AI for digital marketing assets, product visual design, and video content creation), and impact evaluation. The results demonstrated a significant increase in conceptual understanding and technical skills, with the average comprehension score rising from 38.40% in the pre-test to 88.60% in the post-test. Furthermore, 88.89% of participants successfully generated ready-to-use digital marketing asset portfolios using AI tools. This program proved highly effective in providing competitive advantages for tahfiz students to thrive professionally in the digital era while preserving religious values.